2008
DOI: 10.1038/ncpcardio1370
|View full text |Cite
|
Sign up to set email alerts
|

Structural remodeling in atrial fibrillation

Abstract: Atrial fibrillation occurs and maintains itself in the context of a morphologically and functionally altered atrial substrate that can be induced by stressors such as underlying diseases (cardiac or noncardiac) or aging. The resultant structural remodeling is a slow process that progressively affects myocytes and the myocardial interstitium, and takes place from as early as the first days of atrial tachyarrhythmia. The left atrium, and particularly its posterior wall, is the location where remodeling is concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 137 publications
3
89
0
2
Order By: Relevance
“…Recent electrophysiological evidence has indicated that the triggering ectopic foci act on predisposing substrates to initiate single-or multiple-circuit reentry, leading to AF (2). The most important histopathological change in AF is atrial fibrosis (3,4). Accumulation of ECM proteins has been documented in biopsied specimens of atrium from patients with AF (5), and experimental studies using animal models have indicated that interstitial deposition of dense ECM proteins causes separation between bundles of atrial myocytes and disturbs cell-to-cell impulse propagation (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent electrophysiological evidence has indicated that the triggering ectopic foci act on predisposing substrates to initiate single-or multiple-circuit reentry, leading to AF (2). The most important histopathological change in AF is atrial fibrosis (3,4). Accumulation of ECM proteins has been documented in biopsied specimens of atrium from patients with AF (5), and experimental studies using animal models have indicated that interstitial deposition of dense ECM proteins causes separation between bundles of atrial myocytes and disturbs cell-to-cell impulse propagation (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…The most important histopathological change in AF is atrial fibrosis (3,4). Accumulation of ECM proteins has been documented in biopsied specimens of atrium from patients with AF (5), and experimental studies using animal models have indicated that interstitial deposition of dense ECM proteins causes separation between bundles of atrial myocytes and disturbs cell-to-cell impulse propagation (3,4). In addition, atrial fibrosis potentially exaggerates myocardial ischemia by hampering oxygen diffusion and alters the electrophysical and biomechanical properties of atrial myocytes, allowing the initiation and perpetuation of AF (4).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, atrial dysfunction, atrial ischemia, pericarditis, congestive heart failure due to ischemia, atrial reverse remodeling and enhanced sympathetic tone may also play an important role in AF in the setting of STEMI [20][21][22][23][24]. An increased sympathetic tone in STEMI patients is associated with worse outcome after 2 years [25].…”
Section: Incident Af After Stemi and Hsctntmentioning
confidence: 99%
“…Accumulation of ECM proteins has been documented in biopsy specimens of the LA from patients with AF, 9 and experimental studies using animal models have indicated that interstitial deposition of dense ECM proteins causes separation of the bundles of atrial myocytes and disturbs cell-to-cell impulse propagation. 8 Dense and disorganized collagen deposition with apoptosis or necrosis of cardiomyocytes reduces the voltage of the contact atrial electrogram and enlarges the LA volume; that is, electroanatomical remodeling.…”
Section: Electroanatomical Remodelingmentioning
confidence: 99%